Direct CO2-to-DME hydrogenation reaction: New evidences of a superior behaviour of FER-based hybrid systems to obtain high DME yield. (March 2017) - Frusteri, F.; Migliori, M.; Cannilla, C.; Frusteri, L.; Catizzone, E.; Aloise, A.; Giordano, G.; Bonura, G.
Graphical abstract: Highlights: The direct CO2 -to-DME hydrogenation was performed on CuZnZr/zeolite hybrid systems. Home-made zeolites of different structure and acidity were used as oxide carriers. The metal-oxides distribution significantly depends on the zeolite topology. An active effect of the ferrierite on the process productivity was evidenced. Hybrid catalysts showed a superior performance than classical mechanical mixtures. Abstract: The catalytic behaviour of Cu-Zn-Zr/zeolite hybrid systems, in which metallic and acidic functionalities were combined at level of single grain, was evaluated in the direct DME production by CO2 hydrogenation. Catalysts were prepared by co-precipitation of the metals precursors in a slurry of three home-made powdered zeolites, characterized by different dimensional frameworks ( i.e., MOR, FER, MFI). The experiments were carried out in a fixed bed reactor operating at 5.0 MPa and temperature ranging from 200 to 260 °C. By appropriate physico-chemical characterization of systems it was revealed that morphology of zeolite crystallites significantly affects the surface distribution of metal-oxides and the nature of active sites created during the co-precipitation step. The FER zeolite was seen to ensure a better dispersion of cluster oxides, favouring the generation of Lewis basic sites for CO2 activation along with a higher availability of Brønsted acid sites for the MeOH-to-DME dehydration step. The catalytic results clearly evidenced a net difference in behaviour among the investigated hybrid systems, both in terms of CO2 conversion and product distribution. Peculiar structure-activity relationships highlighted the superior performance of CuZnZr-FER catalyst, allowing to reach the highest DME productivity value (≈600 gDME /kgcat /h), as the consequence of better efficiency in mass transferring ensured by neighbouring active sites involved in the reaction mechanism. The stability test evidenced a progressive deactivation not associated to coke deposition or metal sintering, but mainly to water formation which negatively affects the behaviour both of metal-oxide and acid sites controlling the DME synthesis rate.